Research on active and passive schemes for safety improvement of nuclear energy hydrogen production system - Gao, Qunxiang; Sun, Qi; Zhang, Ping; Zhao, Gang; Peng, Wei (Frontiers in Nuclear Engineering, 2024)
Nuclear hydrogen production has the advantages of large-scale and low carbon emissions, and is expected to play an active role in the energy transition process.However, the storage and transportation of hydrogen pose potential risks of leakage and diffusion when connected to high-pressure hydrogen storage tanks and pipelines. To address this concern, this study focused on designing three distinct safety improvement schemes tailored for potential hydrogen leakage accidents. These schemes encompassed a passively distributed arrangement of obstacles (Scheme 1), a passively centralized arrangement of obstacles (Scheme 2), and an active fan array blowing (Scheme 3). Numerical simulation methods were applied on extensive spatial scales for relevant calculations. Our findings revealed that all three schemes effectively reduced the diffusion distance of combustible hydrogen. Specifically, at lower ambient wind speeds, Scheme 1, Scheme 2, and Scheme 3 achieved the shortest diffusion distances of 123 m, 56 m, and 46 m, respectively. Meanwhile, at higher ambient wind speeds, the corresponding distances were 282 m, 100 m, and 79 m. These results collectively offer valuable insights to mitigate the risk of leakage accidents in nuclear hydrogen production systems.